SISTEM INFORMASI MANAJEMEN ASET DAN PENYAJIAN ASET TETAP DALAM LAPORAN KEUANGAN - Siswati, Roro; Riharjo, Iksan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the use of application of asset management system in the management of State Property in the Tenth November Institute of Technology (ITS). The research method has been done by using qualitative descriptive. The data collection has been done by using technique of observation, interview, and documentation. The preparation and the reporting of state property has been carried out by using an application that is made by ITS i.e. ITS Aset Management Information System (SIMAS). The ITS SIMAS is an application which can run the data and the information management that is related to the physical asset particularly in the capital expenditure and has integrated to financial application, approval application, and application SIMAK BMN. The mechanism of presentation and preparation of the reporting of state property the public service agency of ITS has been conformed with the Government Regulation and has been implemented completely the guideline of Accounting and Financial and The Regulation of the Minister of Finance of the Republic of Indonesia.Keywords: Information System, State Property Public Service Agency, Tenth November Institute Of Technology.